A Review of the Role of the Gut Microbiome in Personalized Sports Nutrition - Hughes, Riley L. (Frontiers in Nutrition, 2020)
The gut microbiome is a key factor in determining inter-individual variability in response to diet. Thus far, research in this area has focused on metabolic health outcomes such as obesity and type 2 diabetes. However, understanding the role of the gut microbiome in determining response to diet may also lead to improved personalization of sports nutrition for athletic performance. The gut microbiome has been shown to modify the effect of both diet and exercise, making it relevant to the athlete’s pursuit of optimal performance. This area of research can benefit from recent developments in the general field of personalized nutrition and has the potential to expand our knowledge of the nexus between the gut microbiome, lifestyle, and individual physiology.